The Context Study of Collaboration in Prototype City of Agricultural Processing Industry Project, Nongjik District, Pattani Province - Jiansuwannapas, Yutthakij; Suebvises, Ploy (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2023)
This article aims to study the Processed Agricultural Products Industry Model City of Nongjik District, Pattani province, based on the Collaborative Governance theory with the following objectives: 1) to study the conditions that lead to collaboration and the Collaborative Governance theory, 2) to analyze the collaboration based on the Collaborative Governance theory. and 3) to compile suggestions and directions in improving the management of urban development in the future. This research is qualitative research consisting of 17 main important informants from the government, business, and public sectors, divided into three levels: the policy level, the policy control level, and the implementation level. The research consists of a documentary study, in-depth interviews, and a field study using questionnaires and semi-structured interview methods. The analysis was done through content analysis. The result showed that the southern provinces have been facing poverty, a lack of knowledge in careers, and unrest caused by the conflict of ethnicity, religion, and the delay in the judicial process that led to the lack of trust in the government. The government has the policy of creating a pilot model city by choosing Nongjik district as one of the three districts with the goal of developing into a processed agriculture model city due to the potential of the area.